Biguanides enhance antifungal activity against Candida glabrata. Issue 1 (31st December 2018) - Xu, Shuying; Feliu, Marianela; Lord, Allison K.; Lukason, Daniel P.; Negoro, Paige E.; Khan, Nida S.; Dagher, Zeina; Feldman, Michael B.; Reedy, Jennifer L.; Steiger, Samantha N.; Tam, Jenny M.; Soukas, Alexander A.; et al.
ABSTRACT: Candida spp . are the fourth leading cause of nosocomial blood stream infections in North America. Candida glabrata is the second most frequently isolated species, and rapid development of antifungal resistance has made treatment a challenge. In this study, we investigate the therapeutic potential of metformin, a biguanide with well-established action for diabetes, as an antifungal agent against C. glabrata . Both wild type and antifungal-resistant isolates of C. glabrata were subjected to biguanide and biguanide-antifungal combination treatment. Metformin, as well as other members of the biguanide family, were found to have antifungal activity against C. glabrata, with MIC50 of 9.34 ± 0.16 mg/mL, 2.09 ± 0.04 mg/mL and 1.87 ± 0.05 mg/mL for metformin, phenformin and buformin, respectively. We demonstrate that biguanides enhance the activity of several antifungal drugs, including voriconazole, fluconazole, and amphotericin, but not micafungin. The biguanide-antifungal combinations allowed for additional antifungal effects, with fraction inhibition concentration indexes ranging from 0.5 to 1. Furthermore, metformin was able to lower antifungal MIC50 in voriconazole and fluconazole-resistant clinical isolates of C. glabrata . We also observed growth reduction of C. glabrata with rapamycin and an FIC of 0.84 ± 0.09 when combined with metformin, suggesting biguanide action in C. glabrata may be related to inhibition of the mTOR complex. We conclude that the biguanide class has direct antifungal therapeutic potential and enhances the activity of select antifungals in the treatment of resistant C. glabrata isolates. These data support the further investigation of biguanides in the combination treatment of serious fungal infections.